2006
DOI: 10.1017/s0022215106001149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes mellitus on deep neck infection

Abstract: Diabetic DNI differs from non-diabetic DNI in several aspects and is associated with a higher morbidity. A greater than normal haemoglobin A1c level was commonly observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 8 publications
5
35
2
3
Order By: Relevance
“…From the above comparisons, diabetics had prolonged hospitalizations similar to many studies, [2,3,15,16,17] needed surgical intervention more often, [3] showed poor response to conservative medical management, [15,17] and had higher chance of developing complications. [3,15,17] Hence, diabetics with DNI must be managed more aggressively with medical and surgical intervention and careful blood glucose monitoring. [17] Clinical Features According to most of the recent studies, pain and swelling of the neck are the most prevalent symptoms.…”
Section: Co Morbiditiessupporting
confidence: 55%
See 4 more Smart Citations
“…From the above comparisons, diabetics had prolonged hospitalizations similar to many studies, [2,3,15,16,17] needed surgical intervention more often, [3] showed poor response to conservative medical management, [15,17] and had higher chance of developing complications. [3,15,17] Hence, diabetics with DNI must be managed more aggressively with medical and surgical intervention and careful blood glucose monitoring. [17] Clinical Features According to most of the recent studies, pain and swelling of the neck are the most prevalent symptoms.…”
Section: Co Morbiditiessupporting
confidence: 55%
“…[3,15,17] Hence, diabetics with DNI must be managed more aggressively with medical and surgical intervention and careful blood glucose monitoring. [17] Clinical Features According to most of the recent studies, pain and swelling of the neck are the most prevalent symptoms. [2,15,16,18,19,20] In this study, pain was the most common presenting complaint, which was followed by dysphagia and neck swelling.…”
Section: Co Morbiditiesmentioning
confidence: 99%
See 3 more Smart Citations